A simulation-based actuator surface parameterization for large-eddy simulation of propeller wakes. (1st March 2020) - Liao, Fei; Wang, Shizhao; Yang, Xiaolei; He, Guowei
Abstract: The existing actuator surface models for wind turbines, which are developed based on the blade element method using the two-dimensional assumption, cannot be easily applied to some marine propellers of highly three-dimensional geometry. In the present paper, a simulation-based actuator surface parameterization for large-eddy simulation (LES) of propeller wakes with the distributed forces computed using a precursor Reynolds-averaged Navier-Stokes (RANS) simulation is proposed to address this issue. Three different actuator surface models, which apply the RANS computed forces directly on the blade surface and apply the RANS-computed forces with/without averaging in the chordwise direction on the 2-D elements of the thickless actuator surface, respectively, are tested. The mean velocity profiles at downstream locations of the propeller are found to be similar for the three different models. The turbulence kinetic energy (TKE) profiles computed from the three different models, on the other hand, are found to be very different in terms of the location and size of the high TKE region. This study indicates the importance of properly modeling the geometrical and hydrodynamic effects of blade in actuator surface models in order to accurately predict propeller wakes. Highlights: Simulation-based actuator surface parameterization for marine propellers. Large-eddy simulation of propeller wakes on Cartesian grids. Different parameterizations affect turbulence intensities in propeller wakes.